2022
DOI: 10.1177/23333936221094858
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Everyday Life Challenges of Danish Young People With Duchenne Muscular Dystrophy (DMD) on Corticosteroids

Abstract: This study aimed to investigate perspectives on everyday life challenges of young persons with Duchenne muscular dystrophy in Denmark treated with corticosteroids perceived by young persons and their parents to improve rehabilitation interventions. Nineteen semi-structured interviews were conducted: 10 individual interviews with 10 persons with DMD and six individual interviews with parents (five mothers and one father) and three couple interviews (three mothers and three fathers). The analysis was guided by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Granted, these differences are not consistently statistically different throughout the study period. Previous studies of individuals with DMD and their parents reported how parents perceive the challenges faced by individuals with DMD as more severe than the individuals themselves [ 9 ]. It is likely that similar worries influence siblings, which in turn result in lower academic performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granted, these differences are not consistently statistically different throughout the study period. Previous studies of individuals with DMD and their parents reported how parents perceive the challenges faced by individuals with DMD as more severe than the individuals themselves [ 9 ]. It is likely that similar worries influence siblings, which in turn result in lower academic performances.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many individuals have behaviour-and learning difficulties. As a result, individuals with DMD have reduced life expectancy with a median survival age of about 30 years [5][6][7][8] and impaired quality of life and an existential worry about life [9].…”
Section: Introductionmentioning
confidence: 99%
“…Is it better for children to be involved in their parents' hopes for their future when this hope entails a cure that will make a fundamental change in the child – hinting that a life without disability is preferable? Does it harm the child to introduce a little escapism and “dream big” as one parent puts it when the child's disability seems to be in the way of the life they want to lead (Handberg et al, 2022)? Or should parents rather from an early age support the children in forming strong positive disability identities, installing the belief in them that they can live a perfectly full life with their disease?…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was set up in SurveyXact ® , an online secure survey platform (Ramboll Denmark), and developed by the study group based on the results from three semi-structured focus groupinterviews (in review elsewhere) [16] with ambulant and non-ambulant women with NMD. The aim of the focus-group-interviews were to identify problem areas in relation to urinating when not at home and to target questions for the questionnaire.…”
Section: Questionnairementioning
confidence: 99%